ANALISIS TREN CAKUPAN KUNJUNGAN ULANG IBU HAMIL (K4) DI WILAYAH KERJA PUSKESMAS KABUPATEN BANYUMAS TAHUN 2010 - Wiranti, Budi Susetyo; Nurhayati, Siti; Sistiarani, Colti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT Maternal Morality Rate (MMR) is still high in the Banyumas district when compared as decreased as MDG?s target?s. The aim?s of this study was to evaluate the variables that affect the complete visit (K4) coverage and described of trends K4 on the working are health centers in the Banyumas district. The study use a descriptive study with qualitative approach and design of the study was evaluating study. Informans selection used purposive sampling technique. Informans have selected as many as 12 people that consisting of 6 people midewife coordinator, 5 health center head, and a person working at field of maternal and child health in Banyumas county health departemen. Based on these results, 4 variables affected K4 coverage are man, money, material, and method. The quality of antenatal care visith from man (health worker/midwife) is influenced by the competence, skill and responsibility for their work. Implementation of maternal and child health program sourced from the state budget, district budget, and society. Owned facilities and infrastructure have been sufficient to support the ANC but less complete. The method used to increase the K4 coverage are others formed pertnership, set policy, and conduct evaluation scheduled and continuous. Trend of K4 coverage can describe that coverage varies widely, some health centers are always reach the target or even never reach the target or as well as those fluctuated experiencing from year to year on the working are health centers in Banyumas district. The competence and skill are improving for midwife can be done by providing training and continuous evenly. Increased responsibility for thei work can be done with regular and scheduled supervision.   Keyword   : ANC, K4 Coverage, Man, Money, Material, Method.  Kesmasindo, Volume 6, Nomor 2, Juli 2013, Hal 94-109